Effect use of steel fiber on mechanical properties of concrete mixture - Hammood, Rasheed Abed; Sharifah Maszura, Syed Mohsin (IOP Publishing Ltd., 2019)
In this paper the influence of commercialize steel fiber with properties of hooked end with 60 mm length and 0.75 mm diameter on the mechanical properties of concrete with three varied volumes of steel fiber 0%, 1% and 2% by volume were added to concrete mixes have been investigated. The design compressive strength considered was 25 MPa. Cubes specimens of size 100 mm x 100 mm x 100 mm to test the compressive strength were prepared for the time of 7th and 28th day, and flexural specimens with 100 mm x 100 mm x 500 mm were prepared. In this study, after 28 days of curing, compressive and flexural strength were determined. The use of steel fiber has shown a significant change on the mechanical properties of the concrete, in particular the compressive and flexural strength with the increase of the volume fraction of steel fibers. The test results show that the use of steel fiber improves the compressive strength, moreover change the failure type to ductile failures.